2015
DOI: 10.1037/emo0000070
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety and narrowed attentional breadth toward faces.

Abstract: The amount of information that can be perceived and processed will be partly determined by attentional breadth (i.e., the scope of attention), which might be narrowed in social anxiety due to a negative attentional bias. The current study examined the effects of stimulus valence on socially anxious individuals’ attentional breadth. Seventy-three undergraduate students completed a computerized dual-task experiment during which they were simultaneously presented with a facial picture at the center of the screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Also, individual differences in the extent to which people focus their attention on specific stimuli (e.g., threats vs. neutral stimuli) has been associated with differences in fear generalisation (Baker et al 2019). Attention is thought to differ between individuals in terms of both the location of its focus (where one attends to) and its breadth (whether it is broad/global or narrow/local; Yoon et al 2015). The present investigation provides the first examination of attentional breadth to fear generalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, individual differences in the extent to which people focus their attention on specific stimuli (e.g., threats vs. neutral stimuli) has been associated with differences in fear generalisation (Baker et al 2019). Attention is thought to differ between individuals in terms of both the location of its focus (where one attends to) and its breadth (whether it is broad/global or narrow/local; Yoon et al 2015). The present investigation provides the first examination of attentional breadth to fear generalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kircanski et al (2015) found that attention processing differed when processing faces of different emotions. However, findings from other studies suggested that attentional costs in anxious and depressive participants were not modulated by emotional valence (Kaiser et al, 2003;Rossignol et al, 2012;Yoon et al 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Considering these differences, it is possible that, in “natural” scenes, socially anxious individuals do not necessarily generate vivid mental imagery, whereas in “social” situations, they might exhibit vivid imagery. The different functions of neutral and social information in social anxiety were observed in attentional functions ( Moriya and Tanno, 2010 ; Yoon et al, 2015 ). Socially anxious individuals exhibited broadened attentional scope for neutral stimuli (e.g., letters) to process peripheral stimuli, whereas they showed narrowed attention for social stimuli (e.g., faces).…”
Section: Discussionmentioning
confidence: 99%